Neuroadaptations to antipsychotic drugs: Insights from pre-clinical and human post-mortem studies - Amato, Davide; Beasley, Clare L.; Hahn, Margaret K.; Vernon, Anthony C. (Neuroscience and Biobehavioral Reviews, 2017)
Antipsychotic drugs, all of which block the dopamine D2 receptor to a greater or lesser extent, are the mainstay for the pharmacological treatment of schizophrenia. Engaging in a deeper understanding of how antipsychotics act on the brain and body, at the cellular, molecular and physiological level is vital to comprehend both the beneficial and potentially harmful actions of these medications and stimulate development of novel therapeutics. To address this, we review recent advances in our understanding of neuroadaptations to antipsychotics, focusing on (1) treatment efficacy, (2) impact on brain volume and (3) evidence from human post-mortem studies that attempt to dissect neuropathological effects of antipsychotic drugs from organic schizophrenia neurobiology and (4) cardio-metabolic side effects. Our aim is to stimulate discussion on these highly clinically relevant topics and consider how we might use current and evolving knowledge and new methodologies in the fields of neuropharmacology and neuroscience, to advance our understanding of the long-term impact of antipsychotic treatment. Ultimately, this may inform the clinical use of these drugs.
EVALuna2:33383